Energy Management for Sustainable Development - Gokten, Soner; Kucukkocaoglu, Guray (IntechOpen, 2018)
We are more aware of the need to achieve sustainable development than ever before. It is fair to say that two of the most important factors affecting sustainability are the ways of both producing and using energy. In this sense, this book provides a forum to articulate and discuss energy management issues in the frame of achieving sustainable development. And undoubtedly, we are also deeply concerned about these issues in the recent times. This volume contains 6 chapters and is organized into three sections: "Policies and Strategies", and "Technologies and Industries".